2000
DOI: 10.1007/bf02756893
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical amination of unsaturated and aromatic compounds

Abstract: The mechanism and synthetic perspectives of an indirect cathodic amination of unsaturated and aromatic substrates are considered. The influence of experimental conditions on the state and reactivity of the aminating reagent in solution is studied. The key role of the electrolyte acidity and redox properties of the reagents and intermediates in the obtained isomeric composition and the yield of the amination products is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Recombination of this radical and its eventual oxidation can produce N 2 gas (reactions 12 and 13). A small amount of nitrate was produced throughout the experiment, possibly due to the reaction between NH 2 Cl and nitrite or H 2 O. , Organic nitrogen was likely the degradation products from the interaction of NH 2 • and NHCl • with 1,4-D. Another possible pathway is that dissolved O 2 reacts with NH 2 • , forming intermediate products NH 2 O 2 • , which reacted with other radicals such as SO 4 •– , HO • , and Cl • to form nitrate . The formation of NO 2 • from nitrate photolysis subsequently resulted in the formation of organic nitrogen. …”
Section: Resultsmentioning
confidence: 99%
“…Recombination of this radical and its eventual oxidation can produce N 2 gas (reactions 12 and 13). A small amount of nitrate was produced throughout the experiment, possibly due to the reaction between NH 2 Cl and nitrite or H 2 O. , Organic nitrogen was likely the degradation products from the interaction of NH 2 • and NHCl • with 1,4-D. Another possible pathway is that dissolved O 2 reacts with NH 2 • , forming intermediate products NH 2 O 2 • , which reacted with other radicals such as SO 4 •– , HO • , and Cl • to form nitrate . The formation of NO 2 • from nitrate photolysis subsequently resulted in the formation of organic nitrogen. …”
Section: Resultsmentioning
confidence: 99%
“…Lysitin and co‐workers used hydroxylamine (Scheme , 23b ) as a reagent for the amination of aromatic compounds . They successfully aminated anisole ( 23a ), benzene, chlorobenzene, and anilines . In all cases, strong acidic conditions were mandatory for the reactions to take place.…”
Section: Other Functionalitiesmentioning
confidence: 99%
“…Mechanism of the electrochemical amination of the anisole in aqueous and aqueous organic electro lytes including diluted H 2 SO 4 can be represented by the set of equations [3]: cathode: (1) which allows controlling the efficiency of the substitution by Ti(III) regeneration rate without any changes of the electrolyte content is a main difference of electrochemical amination from chemical one. In chemi cal amination [1,2], the addition of commercial Ti(III) solution to the emulsion or solution of anisole decreases molar ratio H 2 SO 4 : H 2 O and concentration of organic solvent and therefore increases the contribution of the reaction (5) into termination of amino radical intermedi ates.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the dependencies of the potential of mercury cathode obtained at 40 and 15°C showed that in acetic acid the decrease of the temperature promotes the decrease of the charge required for finishing the target electrochemical process (see figure). Change of the potential of the mercury cathode during the electrolysis of the system Ti(IV)-NH 2 OH-anisole in the electrolytes containing acetic acid (1, 2) and acetoni trile (3,4) at 15 (1,4) and 40°C (2,3).…”
Section: Efficiency Of Electrochemical Amination Of Anisole In Aqueoumentioning
confidence: 99%
See 1 more Smart Citation